The reliability and validity of Tennessee Self Concept Scale (TSCS) instrument on residents of drug rehabilitation centers - Yusof, Rosdi; Ahmad, Jamaludin; Jailani, Othman (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
This is a descriptive research that evaluates the coefficient reliability and validity of the Tennessee Self Concept Scale (TSCS) instrument. The objective of this research is to prove the extent that TSCS can be used to evaluate the self-concept of drug rehabilitation residents. This research will determine whether its coefficient reliability value match the necessary standard. An instrument is considered as applicable for a research purpose when the reliability coefficient value fulfills the minimum standard (Mohd Majid Konting, 2004). The research is conducted in two drug rehabilitation centers, namely the Sungai Besi and Bachok Rehabilitation centers. The residents of both centers answered questionnaires from the TSCS instrument. The Sungai Besi center consists of male residents while the Bachok center consists of female residents. In summary, the value of coefficient reliability has fulfilled the minimum standard. The overall coefficient results are .855 with .888 for Sungai Besi Center respondents and .789 for Bachok Center respondents. As the reliability value is high it is evidence that the TSCS instrument can successfully be used in drug rehabilitation centers in Malaysia.